Disciplinary Societies, Societies of Control and Societies of Radical Uncertainty - Tagliagambe, Silvano (Scenari, 2023)
Many of the ideas that have given rise to the growth of contemporary knowledge have required a very long time to mature and have only become reality only thanks to the contingent coexistence of perception and imagination, of a sense of reality and a sense of possibility, of individual inventiveness, favourable demand contitions, and receptive cultural, social and institutional environments. In order to check the concreteness and effectiveness of long-term visions, those that have a texture made up of coherence and rigour, but also of imagination, uncertainty and risk, and that go too far in time to be evaluated with direct and immediate criteria of yield, in which the risk is calculable, we can usefully resort to feedback mechanism, at the basis of cybernetics. Keeping together, in constant reciprocal tension, and using alternatively the sense of possibility, oriented towards the long term, and the sense of reality, or to be more precise of effectivity, which refers to the ‘here’ and ‘now’, the latter can be used as an intermediate control instrument, regulated precisely by feedback, of visions and strategies that look to a more distant future. The paradigm of digital twins teaches operationally to do just that: mathematical models, Big Data and sophisticated algorithms of Artificial Intelligence make it possible to construct the hyper-reality of the Metaverse, a parallel virtual dimension, reconstructible with great accuracy and realism, and which must be used not to escape from reality, nor even for purely recreational purposes, but to reason in predictive mode, checking ex ante the validity of decisions taken and choices made.